Development of a baseline-temperature correction methodology for electrochemical sensors and its implications for long-term stability. (December 2016) - Popoola, Olalekan A.M.; Stewart, Gregor B.; Mead, Mohammed I.; Jones, Roderic L.
Abstract: Recent studies have shown that (three-electrode) electrochemical sensors can be utilised for air quality monitoring and exposure assessment. The long-term performance of these sensors is however, often limited by the effects of ambient meteorological parameters on the sensor baseline, in particular temperature. If electrochemical (EC) sensors are to be adopted for air quality measurement over extended periods (months), this effect must be accounted for. Recent long-term, ambient measurements of CO, NO and NO2 using EC sensors have revealed that temperature (and relative humidity (RH)) had an effect on the baseline which was more pronounced in the case of NO sensors with coefficient of determination, R 2 of 0.9 when compared to CO and NO2 with R 2 < 0.2. In this paper we present a correction methodology that quantifies this effect (referred to here as fitted baseline), implementing these correction on the EC measurements. We found that EC sensors corrected for baseline-temperature effect using the method describe in this paper show good agreement when compared with traditional reference instrument. The coefficient of determination R 2 of 0.7–0.8 and gradient of 0.9 was observed for baseline-temperature corrected NO compared to R 2 = 0.02 prior to baseline-temperature correction. Furthermore, the correction methodology was validated by comparing the temperature-baseline with proxy temperature compensating measurements obtained from the fourth electrode of a set of novel four-electrode electrochemical sensors. A good agreement (R 2 = 0.9, with gradients = 0.7–1.08 for NO and 0.5 < R 2 < 0.73 for CO) was observed between temperature fitted baselines and outputs from the fourth electrodes (also known non-sensing/auxiliary electrode). Meanwhile, the long-term stability (calibrated signal output) of temperature-corrected data was evaluated by comparing the change in sensor gain to meteorological parameters including temperature, relative humidity, wind speed and wind direction. The results showed that there was no statistically significant change in sensitivity (two-sided t -test, p = 0.34) of the temperature-corrected electrochemical sensor with respect to these parameters (over several months). This work demonstrates that using the baseline-temperature correction methodology described in this paper, electrochemical sensors can be used for long-term (months), quantitative measurements of air quality gases at the parts per billion volume (ppb) mixing ratio level typical of ambient conditions in the urban environment. Highlights: Temperature correction of low cost air quality sensors. Developed a robust baseline-temperature correction methodology. Methodology shown to be reproducible for different gas species. Temperature corrected data show good agreement with reference instrument. Long term gain/sensitivity of sensors not affected by meteorology.